Short Video Marketing: Strategies For Increasing Tourism In Indonesia - Bakti, Surya; Marpaung, Durahman (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to determine (1) the existence and potential of short video marketing in promoting Indonesian tourism; and (2) SWOT analysis of short video marketing as a strategy to increase Indonesian tourism. This research is qualitative research with descriptive methods. The results of this research show that (1) short video marketing in Indonesian tourism promotion is managed by the Ministry of Tourism and Creative Economy to display the branding of 'Pesona Indonesia' and 'Wonderful Indonesia', short video marketing has the potential to fulfill tourists' needs for information about a tourism destination in Indonesia; and (2) short video marketing strategy to increase Indonesian tourism based on SWOT analysis consisting of SO strategy in the form of planning short video marketing content, WO strategy in the form of publishing short video marketing content, ST strategy in the form of stakeholder collaboration supporting short video marketing for sustainable tourism, and strategy WT is in the form of educating tourism service actors to create short video content as tourism marketing.